2001
DOI: 10.1034/j.1600-0773.2001.088001034.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Toxicity in the Pregnant Rabbit by theClass III Antiarrhythmic Drug Sotalol

Abstract: The purpose of this study was to investigate the potential of sotalol to cause developmental toxicity in the pregnant rabbit. Sotalol is a b-adrenoceptor blocking drug which also has class III antiarrhythmic properties via Ikr channel blockade. Experiment 1: Nine pregnant New Zealand White rabbits were given doses of either 300, 225, or 150 mg/kg of sotalol during gestational days, called Days, 13-16 which resulted in total litter loss. Experiment 2: A single dose of sotalol, 100 or 150 mg/kg was administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Class III antiarrhythmic agents such as sotalol have been shown to increase the incidence of embryonic deaths in animal studies. 16 Of live offspring, the 7% rate of cardiac anomalies is identical to a previously reported recurrence rate in mothers with congenital heart disease 4 and 10-fold higher than the population at large. 17 The primary cardiac event rate of 19.4% observed in this study is comparable to the 23.5% incidence described in a large cohort of pregnant women with heart disease, of whom 19.1% had underlying congenital heart malformations.…”
Section: Discussionsupporting
confidence: 70%
“…Class III antiarrhythmic agents such as sotalol have been shown to increase the incidence of embryonic deaths in animal studies. 16 Of live offspring, the 7% rate of cardiac anomalies is identical to a previously reported recurrence rate in mothers with congenital heart disease 4 and 10-fold higher than the population at large. 17 The primary cardiac event rate of 19.4% observed in this study is comparable to the 23.5% incidence described in a large cohort of pregnant women with heart disease, of whom 19.1% had underlying congenital heart malformations.…”
Section: Discussionsupporting
confidence: 70%
“…Sotalol may be teratogenic, although data are inconclusive. 52,53 Given these ambiguities it is not a first choice antiarrhythmic; however in some difficult cases its use is warranted and complications are rare. Close fetal monitoring is essential.…”
Section: Cordina and Mcguire Arrhythmias In Pregnancymentioning
confidence: 99%
“…We showed that there was a significant difference between the mean number of viable fetuses in the treated pregnant females and those in the control pregnant rats. This corresponded with Skold and Danielsson [47] who investigated the potential of sotalol, which is a 3-adrenoceptor blocking drug that has family III antiarrhythmic characteristics through IBr channel blockade that can lead to toxicity during the pregnancy of rabbits. This study's results revealed that only one dose of sotalol, 100 or 150 mg/kg on Days 8, 9, or 10 generated a slightly greater rate of dead embryos parallel to historic control animals.…”
Section: Discussionmentioning
confidence: 58%